Produção de conhecimento interdisciplinar: um mapeamento da colaboração científica no programa de pós-graduação em ciência, tecnologia e sociedade da UFSCar - Faria, Rodrigo Justulin de (2019)
People who receive relevant information are able to use them in their decision-making, become more flexible, and are able to visualize previously unexplored paths, thereby projecting new horizons. In business, knowledge management, more than people do, involves their knowledge and skills. Organizations depend on how people use their knowledge to address new issues and trends collectively in their work environments. In this context, the general objective of this research is to propose a conceptual model of scientific collaboration that can show how or not the interdisciplinarity was established during the 10 years of research development in the Postgraduate Program in Science, Technology and Society of Federal University of São Carlos - UFSCar. The obtained results show interactions, associating the individual intellectual capital of each member of the Program, and, with this, it foments new ideas and solutions giving greater visibility to the collaborative scientific production of the Program, making it better positioned in the Brazilian educational scenario. The results also show that there are other sectors in which knowledge management can be studied and applied, for example, in academic institutions, allowing the management of the production of interdisciplinary scientific knowledge. In this way, to increase the understanding of the way in which the knowledge is generated by the researchers, teachers and students, as well as the forms of internal and external collaboration are given to the Program. Based on this understanding, the construction of a conceptual model of scientific collaboration for the production of interdisciplinary knowledge allows not only to contribute to better explain the trajectory of the scientific production of the Program, up to this present moment, but also to gather subsidies to design its future, in a perspective of the generation of a collaborative and consequently, interdisciplinary knowledge.